Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1161/circulationaha.104.530931
|View full text |Cite
|
Sign up to set email alerts
|

Total Cavopulmonary Connection Flow With Functional Left Pulmonary Artery Stenosis

Abstract: Background-In our multicenter study of the total cavopulmonary connection (TCPC), a cohort of patients with long-segment left pulmonary artery (LPA) stenosis was observed (35%). The clinically recognized detrimental effects of LPA stenosis motivated a computational fluid dynamic simulation study within 3-dimensional patient-specific and idealized TCPC pathways. The goal of this study was to quantify and evaluate the hemodynamic impact of LPA stenosis and to judge interventional strategies aimed at treating it.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 29 publications
(32 reference statements)
2
72
2
Order By: Relevance
“…Recently, EL has been introduced into clinical applications (eg, to estimate the outcomes of artery anastomosis in cardiovascular surgery). 15,19 In this study, we have introduced the EL concept to predict the risk of aneurysmal rupture. The results demonstrated that the EL created when flow passes through the aneurysm was significantly higher in ruptured-IAs than in unruptured-IAs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, EL has been introduced into clinical applications (eg, to estimate the outcomes of artery anastomosis in cardiovascular surgery). 15,19 In this study, we have introduced the EL concept to predict the risk of aneurysmal rupture. The results demonstrated that the EL created when flow passes through the aneurysm was significantly higher in ruptured-IAs than in unruptured-IAs.…”
Section: Discussionmentioning
confidence: 99%
“…The patientspecific TCPC CFD analysis methodology and in vitro validations of these techniques have been described in previous studies (27,29,42). For each patient geometry, blood flow was modeled at baseline steady-state flow conditions by setting SVC and IVC flows to values derived from PC MRI averaged over the cardiac cycle.…”
Section: ϫ2mentioning
confidence: 99%
“…Final mesh numbers and densities utilized for both anatomical models (Table 1) were comparable to the finest mesh sizes that have been used in our previous (steady-state) studies. 22,23,32 The Hex Core meshes were generated in approximately 1 h. This time is similar to that required to generate an unstructured tetrahedral mesh layout, but has the added benefit of containing a core of equally sized hexahedral (brick) elements that covers~80% of the computational domain. Convergence of the Hex Core layout was also considerably faster than that of the tetrahedral mesh layout.…”
Section: Mesh Generationmentioning
confidence: 99%
“…Advances in fluid flow modeling of complex TCPC anatomies is even more critical as new virtual patient-specific surgical planning tools are introduced 28 and proven to be potentially useful in several clinical cases. 22,32 Accurate modeling of the unsteady flow deserves added emphasis as the right-heart bypass and diaphragm movement introduces significant unsteadiness to the otherwise steady single-ventricle venous flow.…”
Section: Introductionmentioning
confidence: 99%